PERTANGGUNGJAWABAN PERAWAT TERHADAP PASIEN DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT - I Putu Harry Suandana Putra (LPPM STIH Awang Long, 2025)
Healthcare services in hospitals require competent healthcare workers in accordance with Law Number 17 of 2023. Medical and healthcare workers receive legal protection when working according to professional standards, while hospitals are responsible for the negligence of their healthcare workers. Nurses, including vocational nurses, nurses, and specialist nurses, work based on hierarchical authority and doctor's instructions. Patients also receive legal protection in receiving safe and quality services. The problem formulation is how are nurses' responsibilities towards patients in healthcare services in hospitals? And how do doctors delegate authority to nurses? The research method used is normative juridical. The results of the research are: The responsibilities of nurses in healthcare services in hospitals include the obligation to comply with professional standards, operational procedures, and the implementation of duties based on the doctor's instructions. Legally, nurses can be held accountable for civil, criminal, and administrative actions for actions that harm patients. The delegation of doctor's authority must be carried out according to the nurse's competence. Hospitals are also responsible for the shortage of healthcare workers based on Law Number 17 of 2023 concerning Health.